CASES OF “DEMONIC POSSESSION” WITH EXAMPLES FROM FOLK NARRATIVES - Berna KOLOT (Fırat University, 2021)
Fear is an emotion that occurs when people perceive threats from the outside world and experience anxiety. Fear that arises in every person for different reasons can also arise in front of supernatural beings that people cannot see, touch, but perceive as a threat. People were afraid of these creatures, which are often considered evil spirits, and tried to protect themselves from them. In that way, people turned to shamans in the pre-Islamic period, while after the adoption of Islam they turned to people like khoja, spiritualists, exorcists for protecting. People who think that jinn also travels around their world believe that jinn can come to where people live at any moment. Therefore, instead of mentioning jinn’s name, people try to prevent this situation by using various nicknames, such as “üçler, iyi saatte olsunlar, dışarşerli". In addition, it is believed that the jinn owns some places in the world, such as “cemeteries, ruins, deserted places”. These supposed genie habitats qualify as “uncanny places”. People elaborate not to pass through them or do not stay there for a long time. Also, when people consciously or unconsciously harm the jinn (somehow to burn or crush them, etc.), it is believed that this will anger the jinn, and they will want to punish people. The physical or spiritual changes observed in people who allegedly come into contact with jinn in folk narratives and beliefs are called “demonic possession”. This study is intended to explain why and how the jinn multiplies people, through sources selected from Anatolian folk narratives.